Evaluasi Penggelaran Aplikasi Di Lingkungan Polri Dalam Rangka Menerapkan Teknologi Informasi Era Police 4.0. - Harvin Raslin (Jurnal Litbang Polri, 2022)
The background of this research is to support one of the Organizational Reform Programs towards Precision Police, namely Changes in Modern Police Technology in the Police 4.0 Era. The discussion uses a qualitative and quantitative approach as well as an Evaluation Theory and Service Excellence approach. The data collection process was carried out using the Focus Group Discussion (FGD) method, filling out questionnaires, interviews and surveys. The targeted respondents are members of the National Police at the Polda and Resort Police levels. The research location consisted of 7 (seven) Polda and 30 (thirty) Polres. The research carried out by the National Police Research and Development Center was carried out from 6 to 30 September 2021 by involving partners as consultants, namely the ICT Division of the Police, the University of Indonesia (UI) and the National Research and Innovation Agency (BRIN). From the implementation of this research, several conclusions have been obtained from 5 (five) main problems raised in the study. The recommendations submitted based on the conclusions of the research are; 1) The ICT Division of the Police needs to develop policy standards and technical guidelines for the development and deployment of applications within the Police, by referring to existing regulations, 2) Applications deployed in the jurisdiction must use the polri.go.id domain and place the application hosting centrally on the data Polri center under the coordination of the Polri ICT Div. 3) Each working unit that develops applications needs to unify and integrate Police Applications through the implementation of Single Sign On (SSO) and the development of Application Programming Interface (API), 4) For applications that do not yet have a menu or function reporting to be added to facilitate data processing for leaders in decision making. 5) The governance of data and information security needs to be applied in the development and deployment of applications by the satker who develops the application in coordination with the ICT Division of the Police. Keywords: Evaluation, Information Technology, Era Police 4.0, Integration, Data Security